Neurodiversity in medical education: How can we improve postgraduate learning for neurodiverse doctors?. (4th May 2022) - Robinson, Daniel
Abstract: Recently, there has been an important drive to increase diversity in medical education, which could potentially translate to improved outcomes for patients. Despite this, evidence on how to support neurodiverse doctors is limited. In this article the author reflects on their experience of postgraduate medical education as a doctor with Attention Deficit Hyperactivity Disorder (ADHD) and considers how the learning environment can be improved to help neurodiverse doctors reach their potential. This includes increasing the diversity of senior role models, using a cognitive apprenticeship model, employing teaching strategies which allow learners to elaborate their individual thought processes, and providing appropriate timely feedback.